1993
DOI: 10.1029/92ja02269
|View full text |Cite
|
Sign up to set email alerts
|

Spectrometric and photometric observations of low‐latitude aurorae

Abstract: The properties of a low-latitude aurora of September 22, 1982, observed with photometers and a spectrograph from McDonald Observatory, Texas, and an all-sky mapping photometer from a site near Boulder, Colorado, are discussed. The dominant emission was [OI] 630 nm with a 630/558 nm emission ratio of 3.8. Other weaker emissions were present that are characteristic of heavy particle aurorae and can be attributed to energetic (keV) ions and neutral atoms from the ring current. The properties of this and other low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
6

Year Published

1995
1995
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 54 publications
(22 reference statements)
0
47
0
6
Order By: Relevance
“…He proposed that the radiation belt can provide the extra energy; the energy is deposited by particle (proton and hydrogen) precipitation, di usion, and other dynamic processes into the low-latitude atmosphere. Indeed, energetic neutral atoms and protons originating in the ring current have been identiÿed as the main source of auroras seen at low and middle latitudes (e.g., Rassoul et al, 1993).…”
Section: The Solar Wind Sourcementioning
confidence: 99%
“…He proposed that the radiation belt can provide the extra energy; the energy is deposited by particle (proton and hydrogen) precipitation, di usion, and other dynamic processes into the low-latitude atmosphere. Indeed, energetic neutral atoms and protons originating in the ring current have been identiÿed as the main source of auroras seen at low and middle latitudes (e.g., Rassoul et al, 1993).…”
Section: The Solar Wind Sourcementioning
confidence: 99%
“…Silverman (1995) establishes a threshold magnetic latitude of about 15 • for a visual auroral event. Rassoul et al (1993) proposed a classification of low-latitude aurorae based on O I 630/558 ratios.…”
Section: Introductionmentioning
confidence: 99%
“…The diffusive emission in the atmosphere at latitudes, where this region maps along the geomagnetic field lines, is caused by the low-energy population. Zverev et al (2012) concluded from model calculations of Rassoul et al (1993) that the auroral luminosity in the form of SAR arcs of low intensity can be related to the precipitation of low-energy electrons from the magnetosphere in the neighbourhood of the plasmapause. The variations of the parameters of corpuscular particles in the inner magnetosphere and in the midlatitude ionosphere are similar: with decreasing latitude one observes a softening of the spectra, a decrease of the energy density of the precipitating flux, and an attenuation of the auroral luminosity.…”
Section: Y I Feldstein Et Al: Auroral Luminosity and Discrete Formsmentioning
confidence: 99%